STUDY AND ANALYSIS OF CLASSIFIERS FOR USE IN EMOTION RECOGNITION - Адикова, А.; Adamova А. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2021)
Today, in the process of obtaining education, and not only, there is a widespread use of the method of communication through online platforms. The massive use of online platforms for communication creates the need for human emotion recognition systems. In facial recognition systems and human emotions, information is collected, analyzed and processed using special methods and learning algorithms. The paper considers and analyzes classifiers for face recognition, such as the HAAR classifier, the feature extraction method, local binary histogram (LBP), neural convolutional networks (CNN), which contribute to the effective implementation of emotion recognition methods.